THE KOMBINASI INTERVENSI ISCHEMIC COMPRESSION TECHNIQUE DAN CRYOTHERAPY SAMA BAIK DENGAN MYOFASCIAL RELEASE TECHNIQUE DALAM MENURUNKAN NYERI SINDROMA MYOFASCIAL OTOT UPPER TRAPEZIUS PADA MAHASISWA FISIOTERAPI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Tri Buana, Ni Made Intansari; Nopi Andayani, Ni Luh; Indrayani, Agung Wiwiek (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 2 (2015): Majalah Ilmiah Fisioterapi Indonesia, 2015)
The myofascial syndrome in upper trapezius muscle is an uncomfortable condition in the upper trapezius muscle area because the trigger point of junction band was activated. It can be happen because the muscle didn't fit in ergonomic position when using the gadget for long time. This study was an experimental study with pre and post control group design. Sampling metodhs used in this study was consecutive sampling. Samples of 20 people were divided into two groups; an intervention group, which were given a combination of ischemic compression technique intervention with cryotherapy and a control group which were given a myofascial release technique, where each group consisted of 10 samples. The results obtained were p=0.001 for intervention group with an average difference of 2.65 ± 1.05 and p=0.003 for control group with an average difference of 1.09 ± 0.85. This suggests that each group experienced a significant decrease in pain. The results of independent t-test showed the results of p=0.10 (p> 0.05) which means that there is no significant difference in the decrease in VAS between the two groups. In conclusions, combination of ischemic compression technique intervention and cryotherapy showed no significant result as myofascial release technique to reducing myofascial pain syndrome of upper trapezius muscle.
Keywords: myofascial syndrome, upper trapezius muscle, cryotherapy, ischemic compression technique, myofascial release technique